(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article discusses the necessity, essence and factors, goals, objectives and problems of managing the practice of taxation of excisable goods at the present stage of liberalization and modernization of the economy in the Republic of Uzbekistan. In the prospects for the socio-economic development of the country, the advantages and features of a creative approach to the effective management of the practice of taxation of excisable goods are scientifically substantiated. The practice of taxation of excisable goods in the tax system of the Republic of Uzbekistan